Crosstalk between the TNF and IGF pathways enhances NF-κB activation and signaling in cancer cells. Issue 5 (October 2015) - Li, Shun; Pinard, Maxime; Wang, Yunling; Yang, Long; Lin, Rongtuan; Hiscott, John; Su, Bing; Brodt, Pnina
Abstract Background The receptor for type I insulin like growth factor (IGF-IR) and NFκB signaling both play essential roles in cancer initiation and progression but relatively little is known about possible crosstalk between these pathways. We have shown that the IGF-IR could rescue lung and colon carcinoma cells from Tumor necrosis factor -α (ΤΝF-α)-induced apoptosis by activating autocrine, pro-survival IL-6/gp130/STAT3 signaling, suggesting that IGF-IR expression could alter NF-κB signaling that is required for transcriptional activation of IL-6. Objective Here we sought to determine if and how IGF-IR signaling promotes TNF-α-induced NFκB activation. Design We used lung carcinoma M-27 and colon carcinoma MC-38 cells to investigate IGF-IR-induced changes to the IKK/IκBα/NFκB pathway by a combination of qPCR, Western blotting, electrophoretic mobility shift assay, a reporter assay and gene silencing. Results We show that in the presence of increased IGF-IR expression or activation levels, nuclear translocation of NFκB in response to TNF-α was enhanced in lung and colon carcinoma cells and this was due to accelerated phosphorylation and degradation of IκBα. This effect was AKT-dependent and mediated via mitogen-activated protein kinase kinase kinase 3(MEKK3) activation. Conclusion The results suggest that ligand-mediated activation of IGF-IR alters NF-κB signaling in cancer cells in an AKT/MEKK3-dependent manner and that temporal aspects of NF-κB activation can regulate the cytokine profile of the tumor cells and thereby, their interaction with the microenvironment.